Novel Antifungal Peptides Produced by Leuconostoc mesenteroides DU15 Effectively Inhibit Growth of Aspergillus niger - Muhialdin, BJ; Hassan, Z; Abu Bakar, F; Algboory, HL; Saari, N (Wiley, 2024)
Indexed by WOS/SCOPUS